BEYOND THE POLEMICS OF TRANSLATION PRINCIPLES: The Critical Issues Involved in Liturgical Reform & Renewal in the Philippines - Asis, Michael Demetrius H. (Asian Horizons, 2015)
The clash of translation principles involved in the translation of official liturgical texts is indicative of an underlying conflict of theologies of divine revelation that, on the one hand, remains largely essentialist and metaphysical, and process-oriented and historical, on the other. This conflict of theologies is symptomatic of an even deeper divide involving what constitutes the most effective way toward accomplishing the highest principle of Vatican II liturgical reform — the full, conscious, and active participation of the faithful in the liturgy. Emphasizing the dynamic and subjective elements of both liturgical translation principles and sacramental efficacy does not contradict, but rather realizes their deepest possible intent.